2023
DOI: 10.1111/1471-0528.17503
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐associated stroke and the recurrence of stroke and other complications in subsequent pregnancies: Population‐based retrospective cohort study

Abstract: ObjectiveTo examine the outcomes of the subsequent pregnancies from women with a previous pregnancy‐associated stroke (PAS) in comparison to matched controls.DesignPopulation‐based retrospective cohort study.Setting and populationAll women with a PAS in Finland 1987–2016 (n = 235) and controls (n = 694).MethodsWe identified all subsequent deliveries and induced and spontaneous abortions for women with a previous PAS and their matched controls from the Medical Birth Register and the Hospital Discharge Register … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A detailed description of the characteristics of recurrent maternal strokes has been published separately. 19 The distribution of subsequent strokes by stroke subtypes is presented in Table 3. Among controls, there were 2 ISs and 2 CVTs, of which one during early pregnancy ending in induced abortion.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the characteristics of recurrent maternal strokes has been published separately. 19 The distribution of subsequent strokes by stroke subtypes is presented in Table 3. Among controls, there were 2 ISs and 2 CVTs, of which one during early pregnancy ending in induced abortion.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of stroke increased ve times during the early postpartum period compared to the rst trimester [23]. According to a Finnish study on Risk Factor Analysis 1987-2016 for stroke through pregnancy and the postpartum period and hypertension problems associated with pregnancy (OR 4.0, 95%) were the most common [24]. The majority of research participants did not disclose any prior history of stroke or risk factor, despite the fact that our study revealed that abortion and eclampsia histories are the most frequent risk factors for stroke during pregnancy and after delivery.…”
Section: Discussionmentioning
confidence: 99%